Pelatihan dan Kaderisasi Penyelenggaraan Jenazah di Dusun Kampung Benit Sungai Mengkuai Kabupaten Bungo - Ani Pajrini; Novita Eka Paradina; Rahayu Saputri; Hasanah Hasanah; Bambang Supriyadi; Adi Kurniadi; Prandika Pratama (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
Community service activity was motivated by the limited number of community members who possessed adequate knowledge and skills in funeral management in Dusun Kampung Benit, Sungai Mengkuai, Bungo Regency, causing residents to depend on only a few individuals whenever a death occurred. This activity aimed to improve community understanding, practical skills, and readiness in bathing, shrouding, praying over, and burying the deceased according to Islamic guidance while preparing local cadres to sustain the practice continuously. The target partners included religious leaders, youth, women, and other community members who had been involved or had the potential to be involved in funeral services at the village level. The implementation stages consisted of needs identification, socialization, material delivery, demonstration, direct practice, mentoring, and participatory evaluation to ensure that participants understood each procedure correctly and confidently. The results showed increased knowledge and technical skills, stronger confidence to participate in funeral management, and the emergence of local cadres who could support the continuity of religious services and strengthen social solidarity within the community.